Stress amelioration response of glycine betaine and Arbuscular mycorrhizal fungi in sorghum under Cr toxicity. - Praveen Kumar (Public Library of Science (PLoS), 2021)
Chromium toxicity is a major problem in agricultural soils that negatively affects a plant's metabolic activities. It reduces biochemical and antioxidant defence system's activities. In search of the solution to this problem a two-year pot experiment (completely randomized design with three replications), in three genetically different varieties of sorghum (SSG 59-3, HJ 513 and HJ 541) under Cr toxicity (2 and 4 ppm) was conducted to determine the effect of glycine betaine (50 and 100mM) and Arbuscular mycorrhizal fungi (AMF) on the antioxidant system (enzymes viz. superoxide dismutase, ascorbate peroxidase, catalase, glutathione reductase, peroxidase and metabolites viz. glutathione, ascorbate, proline, β-carotene) along with Cr accumulation and indices of oxidative stress parameters (polyphenol oxidase, hydrogen peroxide and malondialdehyde) at two growth stages (vegetative and grain filling). According to results; Cr stress (2 & 4 ppm) increased its accumulation and indices of oxidative stresses significantly (p≤0.05) in all varieties of sorghum at both growth stages. However, soil application of glycine betaine (GB) and AMF decreased Cr accumulation and indices of oxidative stress by increasing antioxidant enzymes and metabolites activities at both growth stages in all varieties. The combination of 100mM GB with AMF was observed most significant (p≤0.05) in decreasing oxidative stress and improved the antioxidant system's activities. The SSG 59-3 cultivar showed the lowest Cr accumulation (1.60 and 8.61 ppm), indices of oxidative stress and highest antioxidant system's activity among these three cultivars at both growth stages. Thus, SSG 59-3 was found most tolerant cultivars followed by HJ 513 and then HJ 541. These findings suggest that both GB and AMF, either individually or combined can play a positive role to reduce oxidative stress and increased antioxidant attributes under Cr toxicity in sorghum.